Middle-Class Welfare and Vertical Redistribution in Australia: A Fiscal Incidence Analysis - Tapper, Alan; Fenna, Alan; Phillimore, John (Wiley-Blackwell Publishing Asia, 2015)
Middle-class welfare’ has been a catch-cry in Australian political debate in recent years, the suggestion being that redistributive programs have unduly benefited the ‘middle class’. However, the concept suffers from a lack of definition and the proposition from a shortage of empirical evidence and a rather selective focus. This article uses Australian Bureau of Statistics’ fiscal incidence studies to track trends from 1984 to 2010. From this more comprehensive assessment of ‘who gets what’, we find that not only has there been no shift of net social support towards middle-income groups, but the opposite is true: vertical redistribution has been strengthened.